Muslim Cosmopolitanism - Bruce B. Lawrence (American Journal of Islam and Society, 2018)
Does cosmopolitanism exist in the Muslim world? Does it reflect a distinct ambience in Muslim societies that links to other expressions of cosmopolitanism beyond Islam?